Analisis Penyusunan Pengembangan Bahan Ajar LKPD dalam Mata Pelajaran PAI - Irfan Ahmad Zain; Ibnu Laksana Aulia Ramdani; Muhamad Mugni Sahid; Muhammad Ridho Abdul Rozaq (CV. Creative Tugu Pena, 2024)
The aim of this research is to present the preparation of LKPD development. This article uses a qualitative method, a qualitative approach with the type of research being library research. LKPD can be interpreted as learning resources or teaching materials or supporting facilities that can be used to assist educators in training students' skills in accordance with the objectives that have been set to discover concepts through steps or activities as well as problems or questions that have been prepared. The steps that can be taken in compiling the LKPD are conducting curriculum analysis, curriculum analysis, drawing up a needs map, determining the title of the LKPD and writing the LKPD. In preparing it, there are several concepts that must be taken into account, such as benefits, preparation requirements and structure or format or components. The development of LKPD can be done with the creativity of educators. Developing LKPD in PAI subjects is the task of educators and is expected to direct students to have good attitudes, knowledge and skills, as well as character to create a dignified nation and be able to solve various problems in everyday life. Keywords: LKPD Development, Teaching Materials, Learning Resources